MAKEUP MODIFICATION QUEEN OF HEART IN THE FILM ALICE IN WONDERLAND AS CARNIVAL MAKEUP WITH PHYSIOGNOMY - Mahmudah, Faizatul; Puspitasari, Feny (Home Economics Journal, 2024)
Character make-up is not only a means in films to create fictional characters, but also a component in performing arts which plays a role in enhancing visual aesthetics, artistic expression and overall appeal in works of art such as carnivals, one example of which is the Queen of Heart character in the film Alice in Wonderland. The challenges in creating makeup based on fictional characters adapted using a physiognomy approach are an interesting discussion. The aim of this research is to create a modified design for the make-up of the Queen of Heart character as a carnival make-up with physiognomy. This research uses the content analysis method with the Miles and Huberman data analysis model. The adaptations made to the Queen of Heart's make-up were done without losing its distinctive characteristics so that the source of the idea can still be recognized even though it is displayed in a different make-up. Research and development of the source of the idea of Queen of Heart as carnival make-up carried out by researchers, resulting in similarities, differences, advantages and disadvantages of Queen of heart make-up in films with adaptations.